Determining the number of clusters using nonparametric statistics - Šimoliūnas, Darius (Lietuvos matematikos rinkinys, 1997)
A Gaussian mixture model is investigated in this paper. A method for estimation of unknown number of clusters in the case of equal covariance matrices is discribed. This method is based on the use of projection pursuit. The results of analysis of the method by simulation are shortly discussed.